Progressive rock caught up with mercantile values: the unknown roots of a "quiet revolution" - Pache, Gilles (Technium Social Sciences Journal, 2022)
The paper focuses on a historical phenomenon that has been little studied: the way in which the music industry, particularly the progressive rock movement that emerged from the counterculture in the 1960s, gradually became subject to the laws of marketing. The roots of this “quiet revolution” are studied starting from the sponsorship negotiated by the Pink Floyd, in 1974, with a famous brand of soft drinks called Gini. The band members agreed that a series of concerts would be partially financed by a multinational company, justifying this choice by the desire to reduce the price of tickets for the fans. While the justification is commendable, it is an essential step towards the triumph of the entertainment society dominated by mercantile values. From this point of view, the Pink Floyd/Gini “affair” can be seen as a key moment for the development of modern marketing.